EFFECT OF SALINITY ON OSMOREGULATION AND GROWTH OF BATIK LOBSTER (PANULIRUS LONGIPES) - Haikal, Muhammad Ikal; Fujaya, Yushinta; Trijuno, Dody Dharmawan (Indonesian Aquaculture Society (MAI), 2020)
Salinity is one of the environmental factors that influence the body's physiological processes primarily in the osmoregulation process and impacts on growth. The purpose of this study is to see the impact of salinity on osmoregulation and growth and determine the optimum traffic for the maintenance of Panulirus longipes. This research was conducted in September 2019-January 2020, at the Balai Udang Mata Seed City, Kendari City, Southeast Sulawesi, Indonesia. The salinity tested in this study was 28, 31, and 34o/oo. The results showed that high salinity had an impact on the level of osmotic action obtained, which was higher, but a decrease in the diameter of granulocytes and hyalinocytes was getting smaller. Male lobsters have better adaptability to salinity than females, where the salinity range of 28-34o/oo can still be tolerated by not affecting growth. Conversely, females are strongly affected by salinity and the optimal support for growth is 31o/oo.